An evaluation of online architectural design studios during COVID-19 outbreak. (14th December 2020) - Ceylan, Salih; Şahin, Pınar; Seçmen, Serengül; Somer, Melek Elif; Süher, Kemal H.
Abstract : Purpose: While the COVID-19 outbreak affects all aspects of life in the world, there is also a global impact in the field of education. Within the scope of the measures to control the epidemic, distance education was started shortly after the starting of the spring semester in all primary and secondary schools and universities. In this process, architectural design courses, which are one of the most fundamental courses of architectural education, started to be held in online studios. The purpose of this paper is to investigate the evaluations of architecture students about the online design studio courses carried out during the COVID-19 outbreak. Design/methodology/approach: This research used a qualitative approach to evaluate the ideas of first, second, third and fourth grade students of architectural design studios in the host university. A questionnaire was directed to students in order to see their opinions about the online design studio education. Findings: Results shows that students think the most prominent benefit of online studios appears in the use of digital tools. Another important result is that if they are equipped with the necessary tools and given the chance to realize themselves, students can work efficiently even in the distance education process. Originality/value: This study is important in terms of learning the expectations of students from the online process and to identify important issues that should be considered for the next semesters. In addition, this study will serve as a basis for comparative evaluation of architectural education during and after the epidemic. In this context, the study will shed light on future academic research.